2016
DOI: 10.1097/pep.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Sensorimotor Training for Balance: Pilot Study Results for Children With Fetal Alcohol Spectrum Disorders

Abstract: Preliminary results support improved sensory adaptation, balance, and motor performance post-STABEL, which warrant further study with a larger, randomized sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our review identified 16 school/education-based management interventions [83,84,85,86,87,88,89,90,91,92,93,96,97,98]. Two of the above-mentioned management interventions aimed at improving mathematical skills and behavior in children with FASD [83,87].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review identified 16 school/education-based management interventions [83,84,85,86,87,88,89,90,91,92,93,96,97,98]. Two of the above-mentioned management interventions aimed at improving mathematical skills and behavior in children with FASD [83,87].…”
Section: Resultsmentioning
confidence: 99%
“…We identified an intervention developed to reduce alcohol consumption and alcohol-related negative outcomes among adolescents with FASD [93], a highly motivating modality intervention [85], the classroom language and literacy intervention [86] and group therapy for foster and adoptive caregivers and their children affected with FASD [68]. These interventions reduced the alcohol use and prevented secondary disabilities among adolescents with FASD [70], improved sensory adaptation, balance and motor performance [85], cognitive [86], executive functioning and emotional problem-solving [92] in children with FASD respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation